The phenomenon of chamberness and its incarnation in the chamber music and chamber ensemble: genre-ontological and semantic aspects - Polska, Iryna I. (Linguistics and Culture Review, 2021)
The article is devoted to chamberness identification, its meaning and specifics as a musical phenomenon. The aim of the article is to determine the ontological, semantic and genre specifics of chamberness and the nature of its embodiment in the fields of chamber music and chamber ensemble. The article is based on the integrative approach, proceeding from a combination of general scientific (cultural, phenomenological, historical, comparative) and special art criticism methods and approaches. The author considers chamber music and chamber ensemble as a nature of chamberness incarnation. Phenomenological, ontological, semantic, genre and categorical aspects are fundamental to this study. The substantial foundation of this study is primarily theoretical and phenomenological conception of a chamber ensemble, formulated in the scientific works of the article`s author. The state of the modern Ukrainian Chamberness (Cameralistics) and the Theory of the ensemble are briefly described. The role of musical chamberness category is characterized and its specificity is defined. The problems of definition and differentiation of “chamber music” and “chamber ensemble” concepts are considered. An ontological specificity of chamberness, determined by its human dimension and quantitative and spatial limitations, is determined.